2018
DOI: 10.1016/j.worlddev.2018.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Can farmers adapt to higher temperatures? Evidence from India

Abstract: Projections suggest that the damages from climate change will be substantial for developing countries. Understanding the ability of households in these countries to adapt to climate change is critical in order to determine the magnitude of the potential damages. In this paper, I investigate the ability of farmers in India to adapt to higher temperatures. I use a methodology that exploits short-term weather fluctuations as well as spatial variation in long-run climate. Specifically, I estimate how damaging high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 84 publications
1
41
0
Order By: Relevance
“…Global heating puts large parts of the Indian population at risk, especially people in low-lying, densely populated coastal regions and islands ( Kumar et al, 2006 ), in cities and at industrial sites, already contaminated by particulate air pollution ( Khosla and Bhardwaj, 2019 ; Revi, 2008 ; Guttikunda and Goel, 2013 ). Agriculture, on which the country heavily relies, is expected to experience devastating impacts ( Kumar et al, 2001 ; O'Brien et al, 2004 ; Rama Rao et al, 2016 ; Zaveri et al, 2016 ; Taraz, 2018 ). Based on their income, 70–80% of India's population can be classified as poor, living in households with less than Rs 5000 monthly income or subsisting on less than 3 USD per day.…”
Section: India's Contested Coal Complexmentioning
confidence: 99%
“…Global heating puts large parts of the Indian population at risk, especially people in low-lying, densely populated coastal regions and islands ( Kumar et al, 2006 ), in cities and at industrial sites, already contaminated by particulate air pollution ( Khosla and Bhardwaj, 2019 ; Revi, 2008 ; Guttikunda and Goel, 2013 ). Agriculture, on which the country heavily relies, is expected to experience devastating impacts ( Kumar et al, 2001 ; O'Brien et al, 2004 ; Rama Rao et al, 2016 ; Zaveri et al, 2016 ; Taraz, 2018 ). Based on their income, 70–80% of India's population can be classified as poor, living in households with less than Rs 5000 monthly income or subsisting on less than 3 USD per day.…”
Section: India's Contested Coal Complexmentioning
confidence: 99%
“…Extreme heat remains especially detrimental to wheat production 57 . Prior work has shown that temperature increases due to climate change can reduce global wheat yields by up to 30 percent by mid-century 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we study the relationship between two important adaptation mechanisms used by rural households in India: irrigation; and short‐term migration. Irrigation is one of the most important adaptation methods used by farmers in response to risks associated with rainfall variability with groundwater providing the most reliable source of water (Fishman ; Taraz ). In India, approximately 90 million households utilise some form of groundwater during critical periods of crop growth (Sekhri ).…”
Section: Introductionmentioning
confidence: 99%